Deep trouble II - Stine, R. L. (New York : Scholastic, 1997)
While visiting their uncle's floating lab in the Caribbean, Billy and Sheena discover that the fish in the sea seem to be growing bigger and bigger.
5.2
5-8
Keywords: Fishes -- Fiction; Horror stories; Fishes -- Fiction; Horror fiction; Caribbean Area -- Fiction; Caribbean Area -- Fiction; Fantastic fiction; Horror fiction